BIOPHYSICAL APPROACHES TO UNDERSTANDING VIRUS HOST CELL MEMBRANE FUSION - Abdiganieva Aysuliw; Yuldasheva Gulasal; Sattarov Yorqin Karimovich (Scholars Digest Publishing, 2025)
Virus host membrane fusion is a central step in the life cycle of enveloped viruses, enabling entry of viral genetic material into host cells. This complex process is governed by coordinated protein conformational dynamics, lipid bilayer rearrangements, and biophysical forces acting at membrane interfaces. Modern biophysical techniques, including single molecule force spectroscopy, fluorescence imaging, molecular simulations, and structural biology approaches, have transformed our ability to dissect the mechanistic steps of fusion at high spatial and temporal resolution. In addition, investigations into the roles of lipid composition, membrane curvature, and fusion protein activation have revealed crucial determinants of fusogenicity. This article reviews contemporary biophysical methodologies used to study virus host membrane fusion, summarizes key mechanistic insights across diverse viral families, discusses how these insights inform antiviral strategies, and highlights emerging trends in the field.
Keywords: Viral membrane fusion; biophysics; fusion proteins; lipid interactions; single molecule techniques; antiviral targets.